BAHASA DAN KEKUASAAN: ANALISIS KRITIS TERHADAP DOMINASI BAHASA DALAM MASYARAKAT - Kamaruzzaman -; Iche - (Jurnal Bahasa Indonesia Prima (BIP), 2024)
It critically analyzes the relationship between language and power in the context of language dominance in society. This research explores how language becomes an important tool to reinforce power structures, regulate power relations between individuals and groups, and influence the construction of social identities. Using a critical approach, this research outlines how the selective use of language by dominant groups can suppress and marginalize minority groups, causing inequality in access to resources and opportunities. Historical, political, and social factors in the formation of power structures through language are also analyzed in depth. In addition, the abstract considers the ethical and political implications of language dominance in society, as well as efforts to break this dominance through multilingual advocacy, recognition of linguistic diversity, and promotion of linguistic equality. This research provides a deep insight into how language is not only a tool of communication but also a tool of power that significantly impacts the formation of inclusive or exclusive social structures.